Teknik Konseling dengan Pendekatan Belajar Sosial dalam Meningkatkan Kepercayaan Diri Anak dengan Hambatan Bicara (Speech Delay) - Nurhadi N; Amirah Diniaty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Self-confidence is an essential aspect of children's social and emotional development. Children with speech delay often experience communication difficulties that can negatively affect their self-confidence, limit social interactions, and lead to feelings of insecurity among their peers. Therefore, appropriate counseling approaches are needed to help children develop a positive self-concept and confidence in their abilities. This study aims to describe counseling techniques based on the social learning approach in improving the self-confidence of children with speech delay. The research employed a descriptive qualitative method using a library research approach. Data were collected through the review of various scholarly sources, including books, scientific journals, research articles, and relevant documents discussing counseling, social learning theory, self-confidence, and the characteristics of children with speech delay. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing based on the reviewed literature. The findings indicate that the social learning approach developed by Albert Bandura can be applied in counseling services through modeling techniques, reinforcement, behavioral observation, social skills training, and positive feedback. By observing and imitating appropriate role models and receiving positive reinforcement from their environment, children with speech delay can develop greater courage in communication, improve their social interaction skills, and strengthen their belief in their own abilities. Consequently, counseling techniques based on the social learning approach are considered an effective strategy for enhancing the self-confidence of children with speech delay. The findings are expected to serve as a reference for counselors, teachers, and parents in providing optimal support and guidance for children with speech delay.